Effect of WhatsApp Messenger-based education on the knowledge of health ambassadors about home care for minor illnesses - Fatemeh Abbasian; Mohammad Mehdi Naghizadeh; Leila Ahmadian (BMC Health Services Research)
Abstract Background In the digital era, virtual education has become one of the most effective educational methods, in which, the latest educational materials can be made available to people using social network platforms. Health ambassadors are mediators for transferring health-related knowledge to the public, so, they must be aware of various health topics, such as home care for minor illnesses. This study aimed to determine the effects of social media-based interventions (using WhatsApp) on the knowledge of health ambassadors concerning home care for minor illnesses. Methods This research was an interventional study carried out in 2021 among health ambassadors in the urban and rural areas of Fasa, a city in the southeast of Fars province. In this study, 121 health ambassadors were divided into control and intervention groups. The educational content is designed based on the Encyclopedia of Self-care Guide in Minor Illnesses and was presented in text, image, and video formats via WhatsApp Messenger to the intervention group on a two-day interval for two weeks. The knowledge level was assessed using a valid and reliable questionnaire developed by researchers. Results After education through WhatsApp, the level of knowledge significantly improved in the intervention group from 30.34 ± 5.58 to 44.80 ± 8.49 (P < 0.001). No significant change was observed in the control group, 34.98 ± 7.19 to 35.67 ± 9.66 (P = 0.431). By controlling the effect of gender, age, marital status, occupation, education, and previous knowledge about minor illnesses by regression analysis, there was a significant improvement in knowledge in the intervention compared to the control group. Conclusions Education through WhatsApp messenger elevated the level of knowledge of health ambassadors about minor illnesses. Generally, using communication technologies for healthcare workers can improve patients and their caregiver’s healthcare services and education.